Study of Regional Innovation System (SIDa) in Accelerating RegionalDevelopment in Malang City - Suhartono Winoto; Kumalasari, Ima; Nashihah, Durratun (PANGRIPTA, 2024)
As an acceleration of development, several ministries in Indonesia formed a joint program called Smart City. To accelerate the program, the central government issued a National Innovation System (SINas) policy which was handed down in each region called the Regional Innovation System (SIDa). SIDa is in the form of a roadmap for mapping innovations that must be carried out by local governments as part of development in the region. The method used in this study is a qualitative approach with a desk review study on the 2022 Malang City Government Monev SIDa Final Report document as well as interviews with representatives of Bappeda and the Research and Development Agency to find out the extent of the success of the program formulated with the realization that has been carried out for a period. The results obtained are the preparation of the SIDa roadmap mapped based on the pillars determined to facilitate monitoring and evaluation. It can be concluded that the Malang City Government has provided innovation to every development carried out, so that the needs of the community can be met.